Times they are a-changing’ for Portuguese emigration?: A comparision of emigrants that departure before and after - Candeias, P. (2022)
This paper aims to answer the question: To what extent do the Portuguese emigrants who left after the economic and financial crisis differ from those who left before this turning point? To fulfil this purpose, it is covered some literature on the impacts of this crisis on international migrations as well as some theories about the motivations that lead to emigration. The empirical component of this paper mobilizes data from a questionnaire survey applied to a sample of about 6,000 Portuguese residents in about 100 foreign countries. The field work took place between May 2014 and May 2015 and was applied in a multi-mode strategy, collecting surveys online and in paper-and-pen format. Several characteristics of the respondents are compared taking into account the year of departure from Portugal: before 2008 or after 2009. Furthermore, official statistics are also used to better corroborate the arguments.